Plan estratégico para el incremento de afiliados en el Seguro Social de la Ciudad de Latacunga, 2014 - 2017. - Garzón Garzón, Mónica Patricia (2013)
The Social Security Institute (IESS), seeks to protect people be they public or private undertaking against the contingencies of sickness, maternity, work injury, disability, unemployment, invalidity, old age and death, it should be noted that the population has a contribution to social insurance according to the national Census 2010 is barely INEC of 22.46 % compared to the economically active population of the city of Latacunga, a situation that leads to perform a " STRATEGIC PLAN FOR INCREASING AFFILIATE IN SOCIAL SECURITY LATACUNGA CITY , 2014 - 2017 ", as one of the most significant processes in an organization, is the development of its strategic plan, as is the instance in which the main components are defined as the present, and its future, which will lead the fate of the organization for the next few years, that the effect is to increase its affiliates. Was raised specific objectives as: Analyze the internal and external situation of Social Security in the city of Latacunga, through the SWOT analysis, determining planning bosses philosophical Social Security area of the city of Latacunga well as developing the strategic map employer's Social Security area of the city of Latacunga for the period 2014-2017, through methods and techniques such as observation, questionnaires application, diagnostic procedures. Among the findings, establishing himself as a weakness is the insufficient mobilization for the staff, preventing timely movement to perform their work, as well as that has not been done enough dissemination of services provided by area employers, not being reports and reports made by 100 % compliance of management indicators in the study area, it was established that in some cases and not in others partially takes control and evaluation, this basically because they do not use tools for define problems, and also not evaluated action plans, which employers area has not unified approach on the quality of service which should provide area employers, not all staff have clearly identified their functions, processes and procedures responsible performance, and also that xix there is deficiency in determining the objectives and plans according to the nature, processes and external stakeholders of the department which can accept the hypothesis "The area employer Social Security Latacunga has not defined the steps that allow you to accomplish the strategic goals of the institution" It is recommended to strengthen the human resource scheduled annual training on topics of interest that will expand the service offering and help generate greater expectations for membership, to achieve efficient internal communication and manage systemic processes that generate written records management reports and performance indicators to achieve constantly measure and reach total quality to maintain contact with employers of small, medium and large to generate greater supply of services, which are monitored continuously weaknesses and threats and delegate a manager to take regular monitoring data close to reality, which led to the philosophical approach of area employers, establish strategic objectives framed in increasing membership coverage, improvement of customer service system, consolidating institutional inter- relations as well as improve the image and institutional positioning, proposal to be implemented and socialized as this will Logar institutional development.